Communication Behavior of Genshin Impact Game Addicts - Bangun Waskito Putro; Erfina Nurussa'adah (Journal of World Science, 2025)
The rise in the global popularity of Genshin Impact raises concerns about the impact of addiction on player behavior, especially regarding communication patterns. This research focuses on understanding the factors contributing to changes in communication behavior patterns among individuals addicted to the Genshin Impact game. Employing a case study approach and qualitative descriptive research methods, we aim to analyze this phenomenon through in-depth interviews with five Genshin Impact game addicts, ensuring the accuracy of the data collected. The data will be processed using the analytical theory of Miles, Huberman, and Saldana, as well as the six addictions theory by Iain Brown. The findings indicate that Genshin Impact game addicts experience a euphoria phase, followed by tolerance and salience, leading to changes in their playing time. Despite the negative impacts, such as excessive playing, there are also positive outcomes, such as increased social connections and additional income. In summary, the changes in deviant behavior patterns among Genshin Impact game addicts have both negative and positive impacts.